TOKOH DAN PENOKOHAN DALAM NOVEL SUPERNOVA: INTELIGENSI EMBUN PAGI KARYA DEE LESTARI - Hartati, Asna Sri; Effendy, Chairil; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to describe characters and characterizations which include characters position, relationships and functions between characters, the meaning of texts and implementation in learning Indonesian language and literature. The method in this research is descriptive with qualitative form. The approach used is structural approach. The data collection technique used is documentary study. The data source is a novel Inteligensi Embun Pagi by Dee Lestari. The results of the study are as follows (1) the characters position is a) Gio as Expedition Companies owner and The Asko’s Key Harbinger coded Mist b) Alfa as Andromeda Capital employee and The Asko’s Dream Harbinger coded wave. c) Zarah as a natural photographer and the Asko’s Gate Harbinger coded Particle. d) Elektra as electrapops owner, electric therapists, and the Asko’s Memory Harbinger coded Lightning. e) Bodhi as a backpacker, tattoo artist and The Asko’s Lattice Harbinger Coded Root. (2) The Characters Relations and functions are harbingers who come from the same Cluster called Asko. Their function is to strengthen each character position. (3) The meaning of the text is the Philosophy of Buddhism. (4) The results of this study can be used in learning Indonesian language and literature in 12th grade high schools.Keywoards: Character, Characterization, Novel, Structural